Detection of Three honeybee Viruses in Palestine using RT- PCR - Sawalha, Hazem (مجلة جامعة القدس المفتوحة للبحوث الإنسانية والاجتماعية, 2017)
Honeybee viruses cause a serious problem that beekeepers suffer persistently from, in Palestine. The presence of honeybee viruses is responsible, with other factors for the recurrent apiary collapse. In the current research, adult and immature bee samples collected from Jenin (1214) , Tulkarm (1016) and Nablus (1032) districts were tested for three honeybee viruses using RT- PCR and specific primers. Deformed Wing Virus (DWV) , Acute Bee Paralysis Virus (ABPV) , and Sac Brood Virus (SBV) were detected in the collected samples with different infection levels. The DWV was the predominant virus infecting honeybees in the studied Palestinian territories. Infection frequencies with this virus were 34 - 86% and 13 - 59% for adult bee workers and broods respectively. ABPV was the second most virus attacking bee colonies in the studied regions, followed by SBV. The maximum infections of adult bee workers with ABPV was 22% whereas 18% infection was recorded for SBV. The mixed infection with these viruses elucidates that they act together to cause apiary failure. This is the first report of the detection of bee viruses in Palestine using molecular techniques.